2009
DOI: 10.1016/j.bbmt.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Seeing What's Out of Sight: Wireless Capsule Endoscopy's Unique Ability to Visualize and Accurately Assess the Severity of Gastrointestinal Graft-versus-Host-Disease

Abstract: Early recognition of gastrointestinal graft-versus-host disease (GI GVHD) after allogeneic hematopoietic stem cell transplantation (alloHSCT) is vital to initiation of therapy. However, the most common location, the small bowel (SB), is difficult to access with upper and lower endoscopy (UGE/LGE). Wireless capsule endoscopy (WCE) is a noninvasive technology allowing complete SB evaluation. The capsule location can also be tracked to identify motility derangements. From August 2006 to July 2007, 11 alloHSCT pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Preliminary reports of this technology in the setting of acute GVHD are inconsistent as to the predominance of mucosal findings in the terminal ileum. 18,19 Abdominal computerized tomography in the setting of acute GVHD also fails to demonstrate selective ileal involvement as the most common pattern seen is diffuse involvement of both large and small intestine in 86% of patients. 20 So, although provocative, the report by Kreisel et al provides insufficient reasons to alter our current practice of emphasizing rectosigmoid biopsies.…”
mentioning
confidence: 99%
“…Preliminary reports of this technology in the setting of acute GVHD are inconsistent as to the predominance of mucosal findings in the terminal ileum. 18,19 Abdominal computerized tomography in the setting of acute GVHD also fails to demonstrate selective ileal involvement as the most common pattern seen is diffuse involvement of both large and small intestine in 86% of patients. 20 So, although provocative, the report by Kreisel et al provides insufficient reasons to alter our current practice of emphasizing rectosigmoid biopsies.…”
mentioning
confidence: 99%
“…In two series, 7/9 and 3/7 patients, respectively, with lesions detected by upper and lower endoscopy had more severe lesions detected by SBCE in the small bowel, which were not accessible by conventional endoscopy. In these cases, SBCE made the overall assessment more accurate [287,289]. A normal SBCE study essentially ruled out aGI GvHD effectively changing the therapeutic course [291].…”
Section: Abdominal Painmentioning
confidence: 97%
“…An exact and early diagnosis is important to initiate a specific treatment or adapt the ongoing immunomodulating therapy. In several small series, patients with suspected aGI GvHD underwent SBCE without complications in any stage of the disease with the procedure being well tolerated [287,289,290]. Endoscopic findings correlated with the histopathologic staging.…”
Section: Abdominal Painmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also suggested that rectal biopsy has a high diagnostic yield in GI-GVHD [11][12][13]. However, it was also reported that the initial pathological changes occur in the ileum in patients with acute GI-GVHD, potentially indicating the essential pathogenesis of GI-GVHD [14]. Considering these reports, there have been no established recommendations regarding the optimal site of examination for acute GI-GVHD in the GI tract.…”
Section: Introductionmentioning
confidence: 96%